The mechanism of change of an object criminal influence and the accounting of these features in designs of crime components - Grountov, Igor (Journal of the Belarusian State University. Law, 2019)
A lot of circumstances are determined criminal law essentiality. Constructions of statutes of criminal law as crucial factors govern criminal law essentiality. Special aspects of structure of the criminal law defended object and mechanism of its change by criminal influence must be factored as a crucial thing into designing of a corpus delicti. In article questions of structure of an object of criminal legal protection and the mechanism of change of an object are considered by socially dangerous encroachment. Is shown that during creation of a concrete design of corpus delicti it is necessary to consider features of structure of an object of criminal legal protection and the mechanism of its change by criminal influence.